Performance Optimization of Automotive Air-Conditioning System Operating with Al2O3-SiO2/PAG Composite Nanolubricants using Taguchi Method - Nurul Nadia Mohd Zawawi; Wan Hamzah Azmi; Mohd Fairusham Ghazali; Anwar Ilmar Ramadhan (Automotive Experiences, 2022)
The performance of an automotive air-conditioning (AAC) system is influenced by a variety of operating conditions. This can be addressed by employing optimization techniques that can suggest the appropriate parameters for the best results. In this study, the optimum operating conditions for a composite nanolubricants-fuelled AAC system were investigate using Taguchi's design of experiment approach and analysis of variance (ANOVA). The motor speed value, initial refrigerant charge, and composite nanolubricants composition ratio were chosen as operating parameters to investigate the AAC system performance, focusing on the coefficient of performance (COP) and compressor work. Orthogonal arrays (ORs) L25 (56) was selected to determine the optimum operating parameters of the AAC system. The optimum values for speed, refrigerant mass, and composition ratio were determined to be A4B1C5 (60:40, 900 rpm and 155 g), respectively. The motor speed was the significant factor influencing both COP and compressor performance by 78.13% and 89.29%. A confirmation test was conducted with the optimum levels of AAC system parameters to verify the efficiency of the Taguchi optimization method. The validation between the optimization results and the experimental results yielded a maximum error of 9.85%, indicating that the findings of this investigation were acceptable.